1988
DOI: 10.1152/ajpcell.1988.254.1.c63
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular communication between ciliated cells in culture

Abstract: Cultured mammalian ciliated cells from the respiratory tract respond to mechanical stimulation of their cell surface by displaying a rapid transient increase in beat frequency. Surrounding adjacent and more distal neighboring ciliated cells display a similar frequency response after a short delay that is proportional to their distance from the stimulated cell. To characterize the progression of this communicated response we developed an automated computer-assisted image-analysis system to examine high-speed fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(47 citation statements)
references
References 15 publications
1
42
1
Order By: Relevance
“…One important and relevant distinction between this result and the contrary result reported by Sanderson et al 43 is the magnitude of applied force; Sanderson's work reported pushing a micropipette 6 m into the cell membrane, while the deformation reported here is substantially less.…”
Section: Physical Contact Of a Trapped Particle Against The Cell Membcontrasting
confidence: 89%
“…One important and relevant distinction between this result and the contrary result reported by Sanderson et al 43 is the magnitude of applied force; Sanderson's work reported pushing a micropipette 6 m into the cell membrane, while the deformation reported here is substantially less.…”
Section: Physical Contact Of a Trapped Particle Against The Cell Membcontrasting
confidence: 89%
“…In chromaffin cells, the problem is that pretreatment with neomycin, a drug that blocks IP3 generation, fails to inhibit spontaneous or caffeine-evoked oscillations although it blocks agonist-evoked ones (70). In hepatocytes, the difficulty is that pretreatment with t-butylhydroperoxide induces typical, periodic 25-Mm/sec calcium waves without inducing formation of any inositol polyphosphate (71 (41). This paper argues that the mechanism of calcium oscillations has been highly conserved; however, evolution is an …”
mentioning
confidence: 99%
“…All the physiotherapy interventions, with the exception of PEP, had an oscillation frequency within the 3-17 Hz range shown to facilitate mucociliary clearance [4]. These oscillation frequencies may assist secretion clearance by altering rheology of the mucus [4] and increasing ciliary beat through stimulation of the ciliated epithelial cells [24,25]. The oscillation frequencies of Flutter1 (11.3 Hz) and Acapella1 (13.5 Hz) were close to the cited optimal frequency for secretion clearance (13 Hz) [4,13].…”
mentioning
confidence: 99%